2008
DOI: 10.1109/tmag.2008.2002528
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of High-Density Bit-Patterned Media With Inclined Anisotropy

Abstract: A new method was proposed to realize high areal densities beyond 2 Tbit in 2 for bit-patterned media. Introduction of inclined anisotropy to the media was found to decrease the effect of magnetostatic interaction between the dots at high areal densities. Recording simulation with a perpendicular recording head revealed increased recording shift margins in both down and cross track directions. It was expected that shift margins of greater than 7 nm were expected in the both directions for recording at 2.6 Tbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A perpendicular remanence curve for perpendicular anisotropy medium is also indicated in the figure as a reference. The reverse beginning field, H nr , of the inclined medium is as large as 15.9 kOe which is much larger than that of the referenced perpendicular anisotropy medium as seen in the figure, but this reversal field is increased by the positive magnetostatic interaction between the dots in the negative saturation state (7) . The magnetization curve from random initial magnetization indicated reduced H nr of 14.3 kOe.…”
Section: Remanence Properties Of Mediamentioning
confidence: 78%
See 2 more Smart Citations
“…A perpendicular remanence curve for perpendicular anisotropy medium is also indicated in the figure as a reference. The reverse beginning field, H nr , of the inclined medium is as large as 15.9 kOe which is much larger than that of the referenced perpendicular anisotropy medium as seen in the figure, but this reversal field is increased by the positive magnetostatic interaction between the dots in the negative saturation state (7) . The magnetization curve from random initial magnetization indicated reduced H nr of 14.3 kOe.…”
Section: Remanence Properties Of Mediamentioning
confidence: 78%
“…Previous work suggested that the optimum condition for wider write shift margins was obtained for the media with inclined anisotropy at around 30 degrees from reverse longitudinal direction when a write head field of a shielded planar head for perpendicular recording was used (7) . However, when the inclination of the anisotropy is as large as that, the reversed direction of the anisotropy is preferable in terms of smaller required field for a write head.…”
Section: Simulation Model Of Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that magnetostatic interaction between the dots becomes to dominate the switching field width at high dot densities beyond 2 Tdot/in . However, when the anisotropy axis was inclined from perpendicular direction, the width was drastically reduced [8]. Fig.…”
Section: Design and Effect Of Inclined Anisotropymentioning
confidence: 97%
“…The exchange coupling acts as to reduce the magnetostatic interaction. Moreover, a further simple technique Manuscript of using inclined magnetic anisotropy for the dots was also proposed, which effectively reduces the effect of the magnetostatic interaction on the switching and indicated possibility of realization of high areal densities beyond 2 Tbit/in [8] when a shielded planar head [9] was used. The effect was pronounced for larger inclination of the anisotropy axis from the film normal, which was not explained by the mechanism of the tilted anisotropy media [10].…”
Section: Introductionmentioning
confidence: 99%